The Effect of Investment and Financial Leverage on Firm Value: Evidence from The Casablanca Stock Exchange - Milki, Meryem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
The objective of this research work is to study the impact of financial decisions, notably leverage and the influence of investments on firm value. In this respect, we conduct an econometric analysis using panel data on the basis of a sample of 3 Moroccan real estate companies listed on the Casablanca Stock Exchange during the period 2019-2022. The results show that leverage has a significant negative impact on firm value in long-run, while investment has a positive long-term impact on firm value. The empirical results also show that other factors can have an impact on enterprise value.

ÖZ: Bu araştırma çalışmasının amacı, finansal kararların, özellikle kaldıraç ve yatırımların firma değeri üzerindeki etkisini incelemektir. Bu bağlamda, 2019-2022 döneminde Kazablanka Menkul Kıymetler Borsası'nda işlem gören Faslı 3 şirketten oluşan bir örneklem temelinde panel veriler kullanılarak ekonometrik bir analiz gerçekleştiriyoruz. Sonuçlar, kaldıracın firma değeri üzerinde uzun vadede önemli bir negatif etkiye sahip olduğunu, yatırımın ise firma değeri üzerinde uzun vadede pozitif bir etkiye sahip olduğunu göstermektedir. Ampirik sonuçlar ayrıca diğer faktörlerin de firma değeri üzerinde etkili olabileceğini göstermektedir.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2024. Supervisor: Prof. Dr. Salih Katırcıoğlu.
Keywords: Banking and Finance Department; Energy Stock Markets--Casablanca Stock Exchange; Stock Prices--Monetary Policy--Casablanca; Firm Value, Investment, Financial Leverage, Panel Data